A Case for Product Lines. Issue 1 (13th September 2016) - Nolan, Andy J.; Pickard, Andrew C.; Fisher, Steve; Beasley, Richard
Abstract: It would seem obvious that a business could benefit from a Product Line, but what is the business case, when can we expect benefits and how much do we need to invest? Under what conditions will it not be cost beneficial to adopt a Product Line? A Product Line is complicated, strategic in nature and it is probably beyond the capability of most people to simply "judge" if it is the right strategy. It was evident that in order for Rolls‐Royce to understand Product Lines, and to make the right trade decisions, we would need to develop a Product Line cost/benefit estimation tool. The tool estimated both the costs to develop assets as well as the costs to deploy the assets onto a project. This paper summarizes the estimation tool we developed and some of the conclusions it revealed. Although the concept was used on a Software Product Line, the principles have been duplicated in hardware and Systems Engineering but are not discussed in this paper.